Osteogenic and anti-inflammatory effect of the multifunctional bionic hydrogel scaffold loaded with aspirin and nano-hydroxyapatite - Li, Shaoping; Xiaowen, Yundeng; Yang, Yuqing; Liu, Libo; Sun, Yifan; Liu, Ying; Yin, Lulu; Chen, Zhiyu (Frontiers in Bioengineering and Biotechnology, 2023)
Although tissue engineering offered new approaches to repair bone defects, it remains a great challenge to create a bone-friendly microenvironment and rebuild bone tissue rapidly by a scaffold with a bionic structure. In this study, a multifunctional structurally optimized hydrogel scaffold was designed by integrating polyvinyl alcohol (PVA), gelatin (Gel), and sodium alginate (SA) with aspirin (ASA) and nano-hydroxyapatite (nHAP). The fabrication procedure is through a dual-crosslinking process. The chemical constitution, crystal structure, microstructure, porosity, mechanical strength, swelling and degradation property, and drug-release behavior of the hydrogel scaffold were analyzed. Multi-hydrogen bonds, electrostatic interactions, and strong “egg-shell” structure contributed to the multi-network microstructure, bone tissue-matched properties, and desirable drug-release function of the hydrogel scaffold. The excellent performance in improving cell viability, promoting cell osteogenic differentiation, and regulating the inflammatory microenvironment of the prepared hydrogel scaffold was verified using mouse pre-osteoblasts (MC3T3-E1) cells. And the synergistic osteogenic and anti-inflammatory functions of aspirin and nano-hydroxyapatite were also verified. This study provided valuable insights into the design, fabrication, and biological potential of multifunctional bone tissue engineering materials with the premise of constructing a bone-friendly microenvironment.